Deploying Microsoft System Center Configuration Manager : manage complex and heterogeneous workloads with ConfigMgr 1706 - Doktor, Jacek; Jarosz, Pawel (Packt Publishing, 2017)
Plan, design, and deploy System Center Configuration Manager 1706 like never before, regardless of how complex your infrastructure is About This Book The most up-to-date resource on deploying or migrating to System Center Configuration Manager 1706 within your IT infrastructure Plan, design, and deploy ConfigMgr 1706 with ease, both on primary and multiple-hierarchy sites Master the new features of ConfigMgr 1706, including Windows 10 support Who This Book Is For If you are a system engineer or an administrator planning to deploy Microsoft System Center Configuration Manager 1706, then this book is for you. This book will also benefit system administrators who are responsible for designing and deploying one or more System CenterConfiguration Manager 1706 sites in their new or existing systems. What You Will Learn Install ConfigMgr servers and the necessary roles Design and scale ConfigMgr environments Configure and administrate essential ConfigMgr roles and features Create software packages using .msi and .exe files Deliver detailed reports with an automatic patching process Apply proper hardening on your deployment and secure workstations Deploy operating systems and updates leveraging ConfigMgr mechanisms Create high-availability components using the built-in mechanism for backup and recovery In Detail It becomes important to plan, design, and deploy configurations when administrators know that Configuration Manager interacts with a number of infrastructure components such as Active Directory Domain Services, network protocols, Windows Server services, and so on. Via real-world-world deployment scenarios, this book will help you implement a single primary site or multiples sites. You will be able to efficiently plan and deploy a multiple-site hierarchy such as central administration site. Next, you will learn various methods to plan and deploy Configuration Manager clients, secure them and make the most of new features offered through ConfigMgr 1706 like compliance, deploying updates operating systems to the endpoints. Then, this book will show you how to install, configure, and run SQL reports to extract information. Lastly, you will also learn how to create and manage users access in an ConfigMgr environment By the end of this book, you will have learned to use the built-in mechanism to back up and restore data and also design maintenance plan. Style and approach This step-by-step guide teaches you cool ways to plan, deploy, and configure ...